2013
DOI: 10.5152/dir.2013.067
|View full text |Cite
|
Sign up to set email alerts
|

MRI of bone marrow abnormalities in hematological malignancies

Abstract: Magnetic resonance imaging (MRI) is essential for evaluating bone marrow. Bone marrow undergoes constant modification and its appearance on MRI changes in response. Knowledge of the types of changes and their origins is essential for analysis of MRI findings of bone marrow infiltration with hematological malignancies. This pictorial review describes the MRI pulse sequences used for imaging of bone marrow, and illustrates bone marrow changes due hematological malignancies, including changes following treatment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 18 publications
(11 reference statements)
1
36
0
2
Order By: Relevance
“…For the detection of bone marrow infiltration, before bone destruction has occurred, MRI remains the most sensitive imaging modality . Conventional T 1 ‐weighted spin‐echo sequences have been considered to be the most useful tool for the evaluation of the infiltration of bone marrow in clinical routine along with short tau inversion recovery (STIR), yet there is evidence that the detection rate of bone marrow abnormalities and therapy response using MRI can be enhanced by applying techniques such as DWI and DCE‐MRI …”
Section: Applications Of Quantitative Bone Marrow Mri and Mrsmentioning
confidence: 99%
“…For the detection of bone marrow infiltration, before bone destruction has occurred, MRI remains the most sensitive imaging modality . Conventional T 1 ‐weighted spin‐echo sequences have been considered to be the most useful tool for the evaluation of the infiltration of bone marrow in clinical routine along with short tau inversion recovery (STIR), yet there is evidence that the detection rate of bone marrow abnormalities and therapy response using MRI can be enhanced by applying techniques such as DWI and DCE‐MRI …”
Section: Applications Of Quantitative Bone Marrow Mri and Mrsmentioning
confidence: 99%
“…MRI is a relatively noninvasive and useful modality for visualizing the bone marrow composition and condition, as well as the joints, with high anatomical resolution and excellent soft tissue contrast [7, 8]. In this context, T1WI of bone marrow gives us valuable information to suspect the presence of insidious leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…Diffuse low signal intensity of bone marrow on T1WI is not specific for acute leukemia and can be seen in other conditions, including myelodysplastic and myeloproliferative syndromes, metastasis of lymphoma, and certain solid tumors [7, 8]. Daldrup-Link et al [10] reported that bone marrow with decreased cellularity and subsequent fatty conversion after chemotherapy exhibited an increase in signal intensity on T1WI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The best imaging modality to evaluate bone marrow is MR imaging due to its high resolution 3 . Normal fatty bone marrow in the adult population is hyperintense on T1-weighted images.…”
Section: Introductionmentioning
confidence: 99%